2020
DOI: 10.3390/ijerph17030953
|View full text |Cite
|
Sign up to set email alerts
|

An Overview on the Associations between Health Behaviors and Brain Health in Children and Adolescents with Special Reference to Diet Quality

Abstract: Unhealthy diet has been associated with overweight, obesity, increased cardiometabolic risk, and recently, to impaired cognition and academic performance. The aim of this review is to provide an overview of the associations between health behaviors and cognition and academic achievement in children and adolescents under 18 years of age with a special reference to diet quality. Dietary patterns with a low consumption of fish, fruits, and vegetables, and high in fast food, sausages, and soft drinks have been lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 164 publications
(264 reference statements)
2
45
1
2
Order By: Relevance
“…A recent study on the physical health of Chinese college students reported that the overweight and obesity rates were increasing yearly among the college students [ 3 ]. Remarkably, overweight/obesity in early adulthood are associated with higher risks of cardiovascular disease in late life [ 4 , 5 ], and it also negatively affects academic performance [ 6 , 7 , 8 ] and executive control (EC), becoming evident in accelerated cognitive decline and brain atrophy in later years [ 9 , 10 ]. Executive control plays a pivotal role in executive functions [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study on the physical health of Chinese college students reported that the overweight and obesity rates were increasing yearly among the college students [ 3 ]. Remarkably, overweight/obesity in early adulthood are associated with higher risks of cardiovascular disease in late life [ 4 , 5 ], and it also negatively affects academic performance [ 6 , 7 , 8 ] and executive control (EC), becoming evident in accelerated cognitive decline and brain atrophy in later years [ 9 , 10 ]. Executive control plays a pivotal role in executive functions [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The eating habits and nutritional knowledge acquired during this stage are key factors for the creation of good eating habits in adulthood [ 18 ]. The management of a healthy diet during adolescence can positively affect psychological well-being and the maturation of the brain, since the most important brain structures develop quickly during this period [ 18 , 19 , 20 ]. Therefore, improving the comprehension of eating habits and patterns of healthy lifestyles during this period can help to identify factors that foster good health [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The current study supports and extends previous findings. Habitual diets rich in fish and low saturated fat meats enhance educational attainment (Loughrey et al, 2017;Tapia-Serrano et al, 2021), while consuming HFSS foods, such as fried potatoes, sausages, soft drinks with sugar, chocolate, sweets, ready-to-eat meals, hamburgers, pizza, potato crisps and ice-cream, appears to be detrimental to educational attainment (Naveed et al, 2020). Timing of eating and specifically skipping breakfast (Lien, 2007) were also confirmed as detrimental within this population.…”
Section: Discussionmentioning
confidence: 99%
“…Identifying a nutrient or food that will improve educational attainment and cognitive performance is laudable, but data indicate that a poor diet, defined by high intakes of fat, salt and sugar made up from a combination of foods, is associated with poor cognitive performance (Naveed et al, 2020) and neurobiological deficits (Stadterman et al, 2020). Observational studies have concluded that diets defined by processed foods (Wiles et al, 2009) or skipping meals (Lien, 2007) were associated with behavioural problems (Øverby & Høigaard, 2012) and poor cognitive performance (Pilato et al, 2020).…”
Section: Introductionmentioning
confidence: 99%